SQLE-mediated squalene metabolism promotes tumor immune evasion in pancreatic cancer - Pan, Junchen; Liang, Haixi; Zhou, Lin; Lu, Wenhua; Huo, Bitao; Liu, Rui; Huang, Peng (Frontiers in Immunology, 2024)
BackgroundSqualene epoxidase (SQLE) is a key enzyme in cholesterol biosynthesis and has been shown to negatively affect tumor immunity and is associated with poor outcomes of immunotherapy in various cancers. While most research in this area has focused on the impact of cholesterol on immune functions, the influence of SQLE-mediated squalene metabolism within the tumor immune microenvironment (TIME) remains unexplored.MethodsWe established an immune-competent mouse model (C57BL/6) bearing mouse pancreatic cancer xenografts (KPC cells) with or without stable SQLE-knockdown (SQLE-KD) to evaluate the impact of SQLE-mediated metabolism on pancreatic cancer growth and immune functions. The effect of squalene on tumor growth and immune cells was tested by direct administration of squalene to C57BL/6 mice bearing KPC tumors. Flow cytometry analysis and immunohistochemical (IHC) staining of immune cells from the tumor tissues were performed to evaluate changes in immune function. We also employed RNA-sequencing to analyze the gene expression profiles in pancreatic cancer cells (PANC-1) treated with or without squalene. RT-PCR and Western blot analyses were used to investigate the relevant molecular mechanisms.ResultsWe show that SQLE is significantly overexpressed in pancreatic cancer, and abrogation of SQLE results in a significant increase in squalene accumulation within tumor cells. The elevated squalene inhibits CXCL1 transcription through its impact on the NF-κB pathway via p65, and thus reduces the recruitment of myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs) into the tumor microenvironment. Silencing of SQLE also leads to an increased proportion of CD8+ T cells in the tumor tissues and suppresses tumor growth in vivo. Importantly, direct administration of squalene, the metabolic substrate of SQLE, to immune-competent mice bearing KPC pancreatic cancer tumors causes a substantial decrease in CD206+ TAMs and MDSCs, thus releasing immune suppression and inhibiting tumor growth.ConclusionOur study shows that squalene is an important immune-modulating metabolite that inhibits the infiltration of immune-suppressive cells in TIME, and that SQLE exerts its tumor immune evasion effect by metabolic removal of squalene. Thus, SQLE-mediated squalene metabolic pathway could be a potential target to enhance antitumor immunity in pancreatic cancer.